Unpublished work by Zygmunt Zakrzewski - Jarzęcki, Krzysztof (Acta Archaeologica Lodziensia, 2023)
The article concerns an unpublished article by Zygmunt Zakrzewski regarding coin finds in Kuyavia, Pałuki and Krajna, written in 1938, whose publication was interrupted by the outbreak of World War II.